2011
DOI: 10.1515/zna-2011-0511
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Some Amino Acids with Sodium Dodecyl Sulphate in Aqueous Solution at Different Temperatures

Abstract: The density ρ, and viscosity η of 0.00, 0.05, 0.10, 0.15, and 0.20 mol kg−1 glycine (Gly), dlalanine (Ala), dl-serine (Ser), and dl-valine (Val) have been measured in 0.002 mol kg−1 aqueous sodium dodecyl sulphate (SDS) at 298.15, 303.15, 308.15, and 313.15 K. These data have been used to calculate the apparent molar volume φv, infinite dilution apparent molar volume φv°, and the standard partial molar volumes of transfer φv° (tr), of the amino acids from water to the aqueous SDS solutions. Falkenhagen coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A number of workers [22][23][24][25][26][27][28][29][30] have measured refractive index of liquids and liquids solutions using Abbe Refractometer. When a ray of light passes from one medium to another, it suffers refraction, that is, change of direction.…”
Section: Refractive Index Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of workers [22][23][24][25][26][27][28][29][30] have measured refractive index of liquids and liquids solutions using Abbe Refractometer. When a ray of light passes from one medium to another, it suffers refraction, that is, change of direction.…”
Section: Refractive Index Studymentioning
confidence: 99%
“…Studies on the interaction of amino acids with surfactants can contribute towards an understanding of the surfactants as tools to isolate, solubilize, and manipulate membrane proteins for subsequent biochemical and physical characterization [6][7][8]. Surfactant are the substance which decrease the surface tension of liquids [9][10][11][12][13] and they are used in many biological, agricultural and chemical processes [14][15][16][17][18]. It has been reported that SDS acts as a more potent protein denaturant than urea and guanidine hydrochloride [19].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic tail of CNTs interacts with the hydrophobic CNT surface during their dispersion in water with the help of amphiphilic surfactants, while the hydrophilic head group is oriented into the surrounding aquatic environment. Surfactant molecules form micelles when their concentration rises above the critical micelle concentration (CMC) [11][12][13][14][15]. These micellar assemblies can be found on CNT dispersions and serve to stabilize them [16].…”
Section: Specific Applications Of Surfactants For Dispersing Carbon N...mentioning
confidence: 99%
“…Surfactants, which are also called wetting agents, help to decrease the tension between two liquids by reducing the surface tension of a liquid. [1][2][3][4][5][6][7][8][9][10][11][12][13]. The reduction in interfacial tension allows liquids to spread more easily.…”
Section: Introductionmentioning
confidence: 99%